Effects of mangosteen (Garcinia mangostana L.) on biochemical and morphological changes in liver and kidney of rats fed on high fat diet - Muhamad Adyab, Noratirah Shazlin (2016)
Obesity is not only worldwide concern as Malaysia also faces increase in the prevalence number of obesity. Obesity always leads to adverse health effect, yet, consumption of vegetables and fruits can prevent it. Nonetheless, a lot of Malaysian is not having enough intakes of vegetables and fruits as recommended. Mangosteen, a purple in colour fruit with fleshy white aril is native fruit from Southeast Asia. Mangosteen contains phenolic compounds named xanthones, anthocyanins and phenolic acids and also a good source of fibre, calcium and phosphorus. The present study addressed the body weight effect, anti-inflammatory and anti-oxidative effects of mangosteen aril in rats feed high fat diet. Forty male Sprague Dawley rats were divided into five groups (n=8), which consisted of normal control group (NC), obese control group (OC), obese supplemented with 200 mg/kg mangosteen group (M200), obese supplemented with 400 mg/kg mangosteen group (M400) and obese supplemented with 600 mg/kg mangosteen group (M600). For 10 weeks, all obese groups were given diet high in fat which contain 414.0 kcal/100g, 43% carbohydrate, 17% protein and 40% fat, while, normal control group were given normal diet with 306.2 kcal/100g, 76% carbohydrate, 21% protein and 3% fat. At the end of ten weeks of diet, alls rats were fasted overnight and 4ml of blood were collected from them. For another seven weeks, obese groups supplemented with mangosteen were force feed to correspond mangosteen dosage while control groups were force feed with distilled water as placebo. At the end of seven weeks supplementation period, all rats were sacrificed before blood, liver and kidney were collected. All data were analyzed using one way ANOVA followed by LSD’s multiple range post hoc test. Differences between groups were considered significantly different when p value was less than 0.05. After ten weeks of high fat diet supplementation, all obese group rats had shown significant increment (p<0.05) of body weight, with significant lower food intake yet greater in energy intake than normal control group rats. All obese group rats also had higher total cholesterol level, triglyceride level and plasma glucose level than normal control group rats. Besides that, all obese group rats also had lower total antioxidant status (TAS), glutathione peroxidase (GPx) and superoxide dismutase (SOD) level than normal control group rats. Seven weeks of mangosteen supplementation lead to significant lower (p<0.05) of body weight, total cholesterol level, tumor necrosis factor-alpha level (α-TNF) and interleukin-6 level (IL6) of all mangosteen supplementation groups than obese control group. In mangosteen supplementation of M400 and M600 groups, there was significant lower (p<0.05) LDL level when compared to obese control group. Other than that, all mangosteen supplementation groups also had significantly higher (p<0.05) GPx and TAS level than obese control group. The anti-obesity action of mangosteen aril is possibly via mangosteen bioactive component, xanthones in α-mangostin form. Overall, this study indicates the potential of mangosteen aril as remedies for body weight maintenance, anti-inflammatory and anti-oxidative.